The Oblivion of the Life-World: The correspondence of Alfred Schutz and Talcott Parsons - López, Daniela Griselda (2012)
At the beginning of the 1940s in the United States, an exchange of correspondence took place between two of the great thinkers in Sociology, Alfred Schutz and Talcott Parsons. This correspondence dealt with matters which many deemed to be “the greatest central problems in the social sciences.” The reading of these letters leads one to assume that the focus of both authors was on answering how sociology could be appropriately based on the revision of Max Weber’s classical contribution. However, this interpretation has served as the basis to affirm that Schutz and Parsons revisited Weber’s project from opposing sides by detaching the elements from its main corpus. This leads to not only opposite but antithetical points of view. From this perspective, Schutz is labeled as a subjectivist whereas Parsons is labeled as an objectivist. Strikingly, even Schutz himself dismisses the idea of presenting both authors as antagonists. What’s more, he underlines his purpose as that of complementarity. Here arises an obvious question. If Schutz from the very beginning underlined the idea of complementarity, why then does contemporary sociological theory present Schutz and Parsons’ contributions as antithetical? Taking this question as the starting point, our enquiry allows us to expose the existence of an interpretive scheme in Sociological Th eory that introduces the dualistic dilemma in the analysis of Schutz and Parsons’ epistolary exchange. We will analyze this interpretive scheme’s main features by using the hermeneutical analysis. Then, in order to critically revisit the debate, our research unveils the prejudices involved in this interpretive tradition, highlighting the misunderstandings regarding the dualistic interpretation of Schutz’s work and his links with Parsons. By doing this it makes clear the way in which these interpretations have veiled the original sense of Schutz’s epistolary exchange with Parsons. Thus our paper, being directly opposed to the dominant reading, aims to propose that the debate shouldn’t be seen as a confrontation between subjectivism and objectivism, but as part of Schutz’s project to go beyond the dualism, starting with a phenomenological approach that recovers the life-world as the forgotten foundation of the social sciences.